Recurrent subacute duodenal occlusion - Chavarría, Oscar; Saccone, Rodolfo (Cirugía del Uruguay, 1974)
We have presented a case of a 11 years old patient with occlusive, subacute, relapsing episodes of duodenum and includes a discusion of c!inical, diagnostic and treatement.